2009
DOI: 10.1007/s00421-009-0987-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 20-day ski trek on fuel selection during prolonged exercise at low workload with ingestion of 13C-glucose

Abstract: Fuel selection was measured in five subjects (36.0 +/- 10.5 years old; 87.3 +/- 12.5 kg; mean +/- SD) during a 120-min tethered walking with ski poles (1.12 l O(2) min(-1)) with ingestion of (13)C-glucose (1.5 g kg(-1)), before and after a 20-day 415-km ski trek [physical activity level (PAL) approximately 3], using respiratory calorimetry, urea excretion, and (13)C/(12)C in expired CO(2) and in plasma glucose. Before the ski trek, protein oxidation contributed 9.7 +/- 1.6% to the energy yield (%En) while fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
2
0
3
Order By: Relevance
“…Dans ce type d'activité, les participants sont encouragés à ingérer des glucides, particulièrement si l'exercice est répété sur plusieurs journées . Toutefois, la sélection des substrats à des puissances de travail faibles (∼22-40% VO 2 max ; VO 2 < ∼1.5 L/min) avec l'ingestion de glucides n'a été dé-crite que dans un nombre restreint d'études , 1977Péronnet et al, 2009;. De plus, seulement deux de celles-ci ont rapporté le devenir métabolique des glucides ingérés et des glucides endogènes (Pé-ronnet et al, 2009;, et l'oxydation respective du glucose plasmatique et du glucose provenant du glycogène musculaire n'a été mesuré que dans une étude récente pour une période d'exercice comparativement courte (Péronnet et al, 2009).…”
Section: Contribution De L'oxydation Du Glucose Exogène : Différencesunclassified
See 2 more Smart Citations
“…Dans ce type d'activité, les participants sont encouragés à ingérer des glucides, particulièrement si l'exercice est répété sur plusieurs journées . Toutefois, la sélection des substrats à des puissances de travail faibles (∼22-40% VO 2 max ; VO 2 < ∼1.5 L/min) avec l'ingestion de glucides n'a été dé-crite que dans un nombre restreint d'études , 1977Péronnet et al, 2009;. De plus, seulement deux de celles-ci ont rapporté le devenir métabolique des glucides ingérés et des glucides endogènes (Pé-ronnet et al, 2009;, et l'oxydation respective du glucose plasmatique et du glucose provenant du glycogène musculaire n'a été mesuré que dans une étude récente pour une période d'exercice comparativement courte (Péronnet et al, 2009).…”
Section: Contribution De L'oxydation Du Glucose Exogène : Différencesunclassified
“…Il existe également peu de données systématiques sur l'effet du mode d'administration des glucides exogènes [bolus vs doses (Massicotte et al, 1996a) ; ingestion avant vs pendant l'exercice Caron et al, 2004;Krzentowski et al, 1984a) ; effet de la concentration de la solution ingérée (Jandrain et al, 1989;Jentjens et al, 2004bJentjens et al, , 2006Moodley et al, 1992)] sur leur oxydation. Un certain nombre d'études se sont penchées, par contre, sur l'effet de l'entraînement Jeukendrup et al, 1997;Krzentowski et al, 1984b;Péronnet et al, 2009;van Loon et al, 1999), de l'état nutritionnel (Ravussin et al, 1979), de certains facteurs environnementaux [froid (Galloway et al, 2001), chaud (Jentjens et al, 2006(Jentjens et al, , 2002, hypoxie (Péronnet et al, 2006)] et de certains nutriments ou agents pharmacologiques dont on sait qu'ils interfèrent ou pourraient interférer avec la digestion et l'absorption des glucides et la sélection des substrats [acarbose qui inhibe les glucosidases (Gerard et al, 1986), sodium (Massicotte et al, 1996b) qui pourrait faciliter l'absorption du glucose par le « sodium-glucose transporter 1 » (SLGT1) , métoclopramide qui accélère la vidange gastrique (Massicotte et al, 1996b), acipimox qui bloque la lipolyse (Gautier et al, 1994) ; caféine (Desbrow et al, 2009;Hulston et Jeukendrup, 2008;Yeo et al, 2005)]. …”
Section: Vue D'ensemble Des éTudesunclassified
See 1 more Smart Citation
“…In the only study that we know of in this specific field, Sandbaek, Steine, Røseth, Falch, & Steine (1997) reported that one male (pre-trek run-specific relative VO 2max of ~60 mL•kg −1 •min −1 ) maintained absolute VO 2max , whereas in two other males (pre-trek run-specific relative VO 2max of ~60-67 mL•kg −1 •min −1 ) absolute VO 2max decreased by ~5-7%, following 21 days of unsupported prolonged LIST from the east to the west coast of Greenland (~540 km). In addition to this, Péronnet et al (2009) evaluated the ski trek-simulated oxygen cost (L•min −1 ) in five active males (pre-trek VO 2max unknown) following 20 days of supported (mid-way) prolonged LIST (~2 km•h −1 , ~10 h•day −1 ) from the northern to the southern part of Lake Winnipeg, Canada (~415 km). The results showed no significant alteration in oxygen cost, indicating no change in work economy, following the traverse (Péronnet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, Péronnet et al (2009) evaluated the ski trek-simulated oxygen cost (L•min −1 ) in five active males (pre-trek VO 2max unknown) following 20 days of supported (mid-way) prolonged LIST (~2 km•h −1 , ~10 h•day −1 ) from the northern to the southern part of Lake Winnipeg, Canada (~415 km). The results showed no significant alteration in oxygen cost, indicating no change in work economy, following the traverse (Péronnet et al, 2009). However, as far as the authors know, no studies have examined the short-term development of ski trek-simulated performance and aerobic endurance ( VO 2max , lactate threshold (LT) and work economy) following prolonged LIST in recreational athletes with high aerobic fitness.…”
Section: Introductionmentioning
confidence: 99%